Examination of the Anaerobic Growth of Campylobacter concisus Strains - Hoyul Lee; Rena Ma; Michael C. Grimm; Stephen M. Riordan; Ruiting Lan; Ling Zhong; Mark Raftery; Li Zhang (International Journal of Microbiology)
Campylobacter concisus is an oral bacterium that is associated with intestinal diseases. C. concisus was previously described as a bacterium that requires H2-enriched microaerobic conditions for growth. The level of H2 in the oral cavity is extremely low, suggesting that C. concisus is unlikely to have a microaerobic growth there. In this study, the anaerobic growth of C. concisus was investigated. The growth of fifty-seven oral C. concisus strains and six enteric C. concisus strains under various atmospheric conditions including anaerobic conditions with and without H2 was examined. The atmospheric conditions were generated using commercially available gas-generation systems. C. concisus putative virulence proteins were identified using mass spectrometry analysis. Under anaerobic conditions, 92% of the oral C. concisus strains (52/57) and all six enteric strains grew without the presence of H2 and the presence of H2 greatly increased C. concisus growth. An oral C. concisus strain was found to express a number of putative virulence proteins and the expression levels of these proteins were not affected by H2. The levels of H2 appeared to affect the optimal growth of C. concisus. This study provides useful information in understanding the natural colonization site and pathogenicity of C. concisus.